Staging Christ's passion in eighteenth-century Nahua Mexico - Burkhart, Louise M., 1958- (IMS monograph ;, 2023)
"Staging Christ's Passion in Eighteenth-Century Nahua Mexico explores the Passion plays performed in Nahuatl (Aztec) by Indigenous Mexicans living under Spanish colonial occupation, a unique manifestation of the theatrical performances of Christ's final travails that arose in twelfth-century Europe"--